2015
DOI: 10.1186/s13071-015-1261-z
|View full text |Cite
|
Sign up to set email alerts
|

Attraction and oviposition preferences of Phlebotomus papatasi (Diptera: Psychodidae), vector of Old-World cutaneous leishmaniasis, to larval rearing media

Abstract: BackgroundAs part of a project aimed at developing oviposition attractants for the control and surveillance of Phlebotomus papatasi (a vector of Old-World cutaneous leishmaniasis), we tested the hypothesis that gravid sand flies are attracted to chemical cues emanating from the growth medium of conspecific larvae - predominantly larvae-conditioned host feces that represents a suitable oviposition site. We report the results of a systematic assessment of media from various developmental stages of the sand fly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
6
20
0
1
Order By: Relevance
“…The strong oviposition deterrent effect of second-/ third-instar larvae observed here is particularly interesting because in a previous study [24], we showed that rearing medium of second-/third-instar larvae was the most attractive and oviposition stimulating medium compared with virgin rearing media or rearing media of older stages (note that in those experiments rearing media tested did not contain any larvae). That attraction was shown to be driven by bacterial odorants (unpublished data).…”
Section: Differential Effects Of Conspecific Stagessupporting
confidence: 51%
See 3 more Smart Citations
“…The strong oviposition deterrent effect of second-/ third-instar larvae observed here is particularly interesting because in a previous study [24], we showed that rearing medium of second-/third-instar larvae was the most attractive and oviposition stimulating medium compared with virgin rearing media or rearing media of older stages (note that in those experiments rearing media tested did not contain any larvae). That attraction was shown to be driven by bacterial odorants (unpublished data).…”
Section: Differential Effects Of Conspecific Stagessupporting
confidence: 51%
“…Interestingly, in three other African sand fly species, all conspecific stages, including older larval stages, stimulated oviposition [33]. However, these results might be related to the use of crushed samples possibly releasing their excreta and gut microbes that might be attractive and/or stimulate oviposition [24].…”
Section: Differential Effects Of Conspecific Stagesmentioning
confidence: 92%
See 2 more Smart Citations
“…longipalpis females were stimulated by hexanal and 2-methyl-2-butanol present in chicken and rabbit feces [ 34 ]. The microbial communities on the larval substrates can also play an essential role in the inducement of oviposition by sand fly females [ 35 ]. However, there was no correlation between the gut microbiota of sand flies with chicken shelter or colony substrates.…”
Section: Discussionmentioning
confidence: 99%